Metabolites Reprogramming and Na+/K+ Transportation Associated With Putrescine-Regulated White Clover Seed Germination and Seedling Tolerance to Salt Toxicity - Cheng, Bizhen; Hassan, Muhammad Jawad; Feng, Guangyan; Zhao, Junming; Liu, Wei; Peng, Yan; Li, Zhou (Frontiers in Plant Science, 2022)
Soil salinization is a serious challenge to many countries worldwide. Putrescine (Put) is related to the improvement of seed germination under salt stress, but molecular and metabolic mechanisms are still not fully understood. The objectives of this study were to determine the effect of seed soaking with Put on germination characteristics under salt stress induced by 100 mm sodium chloride (NaCl) and to further analyze subsequent stress tolerance associated with amylolysis, oxidative damage, sodium (Na+)/ potassium (K+) accumulation and transportation, and metabolic homeostasis in white clover (Trifolium repens cv. Haifa) seedlings. The results showed that seed soaking with Put significantly alleviated salt-induced decreases in the endogenous Put content, germination rate, germination vigor, germination index, Rl/SL, and fresh/dry weight of seedlings. Put application also significantly promoted starch metabolism through activating α-amylase and β-amylase activities under salt stress. The metabolomic analysis showed that seed soaking with Put significantly increased the accumulation of polyamines (Put and spermidine), amino acids (γ-aminobutyric acid, glutamate, alanine, proline, citrulline, etc.), organic acids (ketopentanic acid, malonic acid, malic acid, ketopentanic acid, cis-sinapinic acid, etc.), lipids and fatty acids (glycerol, stearic acid, linoleic acid, palmitic acid, etc.), sugars (levoglucosan, fucose, and anhydro-D-galactose), alcohols (myo-inositol, allo-inositol, hexadecanol, and threitol), and other metabolites (thymine, xanthine, adenine, guanine, and glycerol 1-phosphate, etc.) associated with enhanced tricarboxylic acid (TCA) cycle and γ-aminobutyric acid (GABA) shunt contributing to better osmotic adjustment, cell membrane stability, energy supply, and metabolic homeostasis when seeds germinated under salt stress. In addition, Put significantly up-regulated the AsSOS1, NHX6, SKOR, HKT1, and HKT8 expression levels which played critical roles in Na+ rejection and K+ retention resulting in higher K+/Na+ ratio during seed germination under salt stress. The Put-induced up-regulation of HAL2 transcription level could reduce the toxicity of 3′-phosphoadenosine-5′-phosphosulfate (PAPS) in cells. Current findings will provide an integrative understanding of Put-induced salt tolerance associated with amylolysis, metabolic regulation, and ionic homeostasis during seed germination.